2017
DOI: 10.1186/s12943-017-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of long non-coding RNAs in glucose metabolism in cancer

Abstract: Long-noncoding RNAs (lncRNAs) are a group of transcripts that are longer than 200 nucleotides and do not code for proteins. However, this class of RNAs plays pivotal regulatory roles. The mechanism of their action is highly complex. Mounting evidence shows that lncRNAs can regulate cancer onset and progression in a variety of ways. They can not only regulate cancer cell proliferation, differentiation, invasion and metastasis, but can also regulate glucose metabolism in cancer cells through different ways, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
137
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 116 publications
(102 reference statements)
3
137
0
Order By: Relevance
“…This is concordant with recent evidence showing that MALAT1 has a direct oxygen-dependent regulation and could be a useful biomarker of tumor hypoxia [17, 18]. In solid tumors, upregulation of MALAT1 increases anaerobic glycolysis by potentiating the actions of HIF-1α through decreased HIF-1α ubiquitination [19]. In HeLa cells, it has been shown to control the HIF-1α axis under hypoxic conditions in a positive feedback loop [20].…”
Section: Discussionsupporting
confidence: 86%
“…This is concordant with recent evidence showing that MALAT1 has a direct oxygen-dependent regulation and could be a useful biomarker of tumor hypoxia [17, 18]. In solid tumors, upregulation of MALAT1 increases anaerobic glycolysis by potentiating the actions of HIF-1α through decreased HIF-1α ubiquitination [19]. In HeLa cells, it has been shown to control the HIF-1α axis under hypoxic conditions in a positive feedback loop [20].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the malignant progression and high mortality rates associated with these tumors are related to their insidious onset, frequent metastasis and recurrence, and poor prognosis . Treatment on the basis of early diagnosis is still the main approach for achieving long‐term cancer‐free survival . Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Treatment on the basis of early diagnosis is still the main approach for achieving long-term cancer-free survival. [32][33][34][35][36] Although many biomarkers of malignant tumors are currently used in the clinical setting, all of these biomarkers have limitations. Therefore, many studies have focused on identifying more effective biomarkers to improve the early diagnosis of ma- 55 Moreover, hsa_circ_0033155 could serve as a biomarker or therapeutic target in non-small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 An increasing number of studies have showed that lncRNAs function as competing endogenous RNAs (ceRNAs) to sponge microRNAs (miR-NAs) to participate in the occurrence and development of multiple types of human tumors. 6,7 An increasing number of studies have showed that lncRNAs function as competing endogenous RNAs (ceRNAs) to sponge microRNAs (miR-NAs) to participate in the occurrence and development of multiple types of human tumors.…”
Section: Introductionmentioning
confidence: 99%